Assessment of quality of well water in Eloor, Kerala - Divya Rani Thomas (Department of Veterinary Public Health,College of Veterinary and Animal Science, 2010)
A comparative assessment of physical, chemical and microbiological quality of well water from Eloor, an industrial area in Ernakulum District of Kerala, India and Ollukara, a non industrial area, in Thrissur district of Kerala, India, was carried out to correlate the impact of industrialization on quality of well water. A total of 200 well water samples consisting of 100 each from both areas were taken for the study. Of the 100 samples, 25 samples each were collected during four different seasons of the year viz., summer (February), pre-monsoon (March-May), monsoon (June-September) and post-monsoon (October-November), to assess change in the quality of well water with the seasons. Mean temperature of well water was higher in Eloor than in Ollukara. The lowest temperature was recorded during monsoon in Eloor and Ollukara, and the highest temperature was recorded during pre-monsoon in Eloor and summer in Ollukara. Acidic pH was observed in both areas, with significantly lower pH in Ollukara. Higher pH values were observed during monsoon and post monsoon and lower during summer and pre-monsoon seasons. Mean total hardness of water was higher in Eloor than in Ollukara and the difference was highly significant. Highest value of total hardness was observed during summer in Eloor and monsoon in Ollukara. Mean COD of water samples showed no significant difference between two areas. In Eloor, the highest and lowest COD were observed during summer and monsoon, respectively. While in Ollukara, highest and lowest COD were observed during post monsoon and pre monsoon, respectively. Mean nitrate concentration was similar in water samples collected from Eloor and Ollukara with lowest concentration observed during pre - monsoon and summer in Eloor and Ollukara respectively, whereas it was highest during post monsoon in both areas. Mean fluoride concentration in well water samples from Eloor was significantly higher than that of Ollukara and no significant seasonal difference was observed in fluoride concentration in well water from Eloor. However, significant seasonal variations were observed in fluoride concentration in Ollukara viz., lower during monsoon and post monsoon, and higher during summer and pre-monsoon. Mean iron concentration was higher in Eloor and had highly significant difference with mean concentration in Ollukara. Significant difference in mean iron concentrations between four seasons could not be observed in Eloor, whereas in Ollukara, four different seasons showed significant difference. Lower concentration was observed during summer and pre-monsoon and higher during monsoon and post monsoon. A significantly higher lead concentration was recorded in well water from Eloor than that from Ollukara. In Ollukara, there was significant seasonal difference in mean lead concentration with highest during monsoon and the lowest during pre-monsoon seasons respectively. Throughout the entire period of study no mercury could be detected in well water samples from both areas. There was no significant difference in mean zinc concentration between well water samples from Eloor and Ollukara. In Eloor, the concentration in summer season was significantly higher than during other seasons. In Ollukara mean zinc concentration in post monsoon was significantly higher than during other seasons. Mean cadmium concentration was similar in both areas and was found to be significantly higher during monsoon season at both Eloor and Ollukara. It was observed that mean Aerobic Plate Count was higher in Eloor than that of Ollukara and the difference was highly significant. There was no significant difference observed between four seasons in Eloor. In Ollukara, significant difference between seasons could be observed with highest count during summer. The mean coliform count of well water from Eloor was significantly higher than that of Ollukara. There was no seasonal variation in mean coliform count in Eloor. Whereas significant variation in mean colifrom count between seasons was observed in Ollukara with highest count during monsoon and lowest during summer. The mean E. coli count in well water from Eloor and Ollukara did not differ significantly. There was no difference in mean E. coli count between four seasons in well water from Eloor and Ollukara. The mean enterococcal count of well water samples from Eloor and Ollukara did not show significant difference. The mean count was significantly higher in Eloor during summer, but there was no seasonal difference in enterococcal count in Ollukara. From the survey conducted among 25 households having wells in Eloor and Ollukara, it could be concluded that 20 and 100 per cent of households, used well as source of drinking water in Eloor and Ollukara respectively. Eighty percent wells were pucca wells in Eloor, whereas only 60 per cent of wells were pucca in Ollukara. Disinfection of wells was practiced by 48 and 52 per cent respectively in Eloor and Ollukara. Only 32 and 36 per cent wells respectively had distance more than 15 metre from nearest polluting source. Among the major human health problems in Eloor, 88, 72, 60, 40, 12, 4 and 16 per cent of household reported respiratory problems, skin diseases, musculoskeletal diseases, headache, ophthalmic problem, neoplasm and congenital anomalies and mental retardation, respectively, which were suggestive of iron, lead and cadmium toxicity and poor quality of air. Whereas in Ollukara, health problems were comparatively less and only 12 per cent house hold reported respiratory problem. Among the major animal health problems in Eloor were digestive disorders, reproductive disorders, skin diseases and lameness indicating iron, lead, cadmium and fluoride toxicity. Retrospective analysis of cases recorded in Eloor veterinary hospital, from January 2005 to December 2009, also revealed symptoms of iron, lead and cadmium toxicity in animals. It was observed that Kuzhikandam creek in Eloor was heavily polluted and acted as a potent source of groundwater pollution. From the comparative study, it was clear that the groundwater contamination in Eloor was purely chemical of industrial origin, while in Ollukara it was attributed to the soil type and household pollution. Construction of sanitary wells, keeping adequate distance from polluting sources, with adequate platform, drainage and parapet is recommended. Steining of wells and covering the wells with nets should also be adopted. Disinfection of wells with sufficient quantity of suitable disinfectant at regular interval also helps to minimize pollution mainly of microbial origin.